Medium-term tongue carcinogenesis assays: A comparative study between 4-nitroquinoline 1-oxide (4NQO)-induced rat and dimethylbenzanthracene (DMBA)-induced hamster carcinogenesis - Kitakawa, D. [UNESP]; Cabral, L. A. G. [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, D. A. [UNESP] (Elsevier, 2006)
The most used animal models in oral cancer research are the hamster treated by dimethylbenzanthracene (DMBA), and the rat treated by 4-nitroquinoline 1-oxide (4NQO). The purpose of this study was to compare the DMBA-induced hamster tongue carcinogenesis and 4NQO-induced rat tongue carcinogenesis by means of morphological analysis. Male Wistar rats were distributed into three groups of ten animals each and treated with 50 ppm 4NQO solution by drinking water for 4, 12 or 20 weeks. A total of 18 Syrian golden hamsters were submitted to 0.5% DMBA (dissolved in acetone) topical application three times/week for 4, 12 and 20 weeks. The primary histopathological change i.e., hyperplasia and hyperkeratosis, was evidenced after 4 weeks treatment with DMBA. Regarding 12 weeks treatment, 4NQO and DMBA were able to induce morphological changes as depicted by hyperplasia and dysplasia. At 20 weeks, squamous cell carcinoma was found in the majority of animals for both carcinogens used. Taken together, our results suggest that the hamster experimental model disclosed aspects related with tongue carcinogenesis in lesser time than rats. Probably, such discrepancies depend strongly on route of administration and the susceptibility with respect to animal species. © 2006 Elsevier GmbH. All rights reserved.
Keywords: Hamster; Rat; Tongue carcinogenesis; 4 nitroquinoline 1 oxide; acetone; dimethylbenz[a]anthracene; drinking water; animal cell; animal experiment; animal model; animal tissue; bioassay; cancer grading; cancer model; cancer susceptibility; carcinogenesis; controlled study; dysplasia; experimental animal; hamster; histopathology; hyperkeratosis; hyperplasia; male; nonhuman; rat; squamous cell carcinoma; tongue cancer; Animalia; Cricetinae; Mesocricetus auratus; Rattus norvegicus